Alobar Holoprosencephaly with Cyclopia: An In-Depth Exploration - Himani Malviya; Bandana Sharma; Rahul Ray; Anchal Malik (Medicine and Medical Research: New Perspectives Vol. 12, 2024)
Alobar holoprosencephaly (HPE) is a rare lethal congenital anomaly frequently accompanied by other malformations (such as cyclopia) and characterized by large variations in incidence. HPE is the most severe form of holoprosencephaly, a congenital brain malformation caused by incomplete division of the forebrain during early gestation. This results in a single, central brain ventricle, absence of the interhemispheric fissure, corpus callosum, olfactory structures, and non-separation of subcortical nuclei. Cyclopia, a rare and severe facial manifestation of alobar HPE, involves the merging of the eye orbits into a single central cavity, often with a proboscis, and is typically incompatible with life. The condition arises from genetic mutations (e.g., SHH, ZIC2, SIX3, TGIF1), chromosomal abnormalities (e.g., trisomy 13, trisomy 18), and environmental factors such as maternal diabetes, alcohol abuse, and teratogen exposure. Clinical features include severe neurological impairments, developmental delays, seizures, and facial abnormalities. Diagnosis relies on prenatal imaging (ultrasound, MRI) and genetic testing, with most cases resulting in stillbirth or early neonatal death. Management is primarily supportive, focusing on symptom relief and palliative care. This chapter underscores the importance of early detection, prenatal counseling, and multidisciplinary care while advocating for further research into the genetic and environmental contributors to this rare condition to improve diagnostic, preventive, and therapeutic approaches. The prognosis for infants with alobar holoprosencephaly and cyclopia is extremely poor, with most cases resulting in stillbirth or neonatal death. Survivors have profound neurological impairments and very limited life expectancy. The management of this condition is primarily supportive and palliative, focusing on alleviating symptoms, providing nutritional support, managing seizures, and ensuring comfort and quality of life. This chapter emphasizes the need for early detection, prenatal counseling, and a multidisciplinary approach to managing alobar holoprosencephaly with cyclopia. By understanding the genetic, environmental, and clinical complexities of this condition, healthcare providers can better support affected families and explore potential avenues for early diagnosis, prevention, and improved care strategies. Despite advances in medical knowledge, the prognosis remains poor, highlighting the need for continued research into the underlying mechanisms and potential therapeutic interventions for this rare and devastating congenital anomaly.